Comparing the clinical outcomes of single vs. systematic dual stenting strategies for unprotected left main bifurcation lesion: a systematic review and meta-analysis - Meng, Shuai; Kong, Xiangyun; Nan, Jing; Yang, Xingsheng; Li, Jianan; Yang, Shenghua; Zhao, Lihan; Jin, Zening (Frontiers in Cardiovascular Medicine, 2023)
The optimal percutaneous coronary intervention (PCI) strategy for coronary left main (LM) bifurcation lesions remains controversial. This meta-analysis compared the medium and longterm follow-up clinical outcomes of single versus systematic dual stenting strategies of LM bifurcation lesions. Methods: We systematically identified studies published within 5 years comparing single versus systematic double stenting strategies for LM bifurcation lesions. The primary endpoint was medium-term (1 year) and long-term (at least 3 years) all-cause death.Secondary outcomes included major adverse cardiovascular events (MACEs), target lesion revascularization (TLR), overall occurrence of stent thrombosis (ST),cardiovascular (CV) mortality, and myocardial infarction(MI). Results: Two randomized controlled trials and nine observational studies with 7318 patients were included in this meta-analysis. In terms of the medium-term followup clinical outcomes, our pooled analysis showed that use of the systematic dual stenting strategy was associated with a lower ST risk (odds ratio [OR]=0.43, 95% confidence interval [CI]: 0.20-0.89, P=0.02) and cardiac death risk (OR=0.43, 95% CI: 0.21-0.89, P=0.02) compared to the single stenting strategy;there was no significant difference between the two strategies regarding rates of allcause death, MACE, TLR, and MI. Patients with long-term follow-up showed comparable observed clinical outcomes between the two strategies. Most importantly, for patients with true LM bifurcation, the risk of all-cause death, ST, and CV mortality following the systematic dual stenting strategy was significantly lower than the single stenting strategy. Conclusions:For patients with LM bifurcation lesions, both the systematic dual stenting strategy and single stenting strategy demonstrated comparable results in terms of all-cause mortality during medium-term and long-term follow-up.However, the systematic dual stenting strategy showed a tendency towards lower incidence of ST and CV mortality compared to the single stenting strategy during medium-term follow-up.Consequently, the systematic dual stenting strategy yielded superior clinical outcomes for patients with LM bifurcation lesions.